Lao People's Democratic Republic : Staff Report for the 2001 Article IV Consultation and Request for A Three-Year Arrangement Under the Poverty Reduction and Growth Facility. (IMF Staff Country Reports; Country Report, 2002)
This paper examines Lao People's Democratic Republic's 2001 Article IV Consultation and Request for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility (PRGF). Over the past 18 months, the Lao authorities have acted decisively to reduce inflation from triple- to single-digit levels. Monetary and fiscal policies were tightened along the lines recommended in the 1999 Article IV Consultation. With these positive results, the authorities have now requested a new three-year PRGF arrangement to solidify macroeconomic stabilization and restart structural reform.